2021
DOI: 10.1186/s40662-021-00244-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a classification system based on corneal biomechanical properties using artificial intelligence predicting keratoconus severity

Abstract: Background To investigate machine-learning (ML) algorithms to differentiate corneal biomechanical properties between different topographical stages of keratoconus (KC) by dynamic Scheimpflug tonometry (CST, Corvis ST, Oculus, Wetzlar, Germany). In the following, ML models were used to predict the severity in a training and validation dataset. Methods Three hundred and eighteen keratoconic and one hundred sixteen healthy eyes were included in this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Corneal topography and tomography were obtained through Pentacam HR (Oculus, Wetzlar, Germany), which uses the Scheimpflug imaging technique to present indices with acceptable accuracy and repeatability ( 23 ). The following parameters were evaluated in the current study: corneal thickness (apex corneal thickness: ACT; pupil corneal thickness: PCT; thinnest corneal thickness: TCT), keratometry (flat keratometry: K1; steep keratometry: K2; mean keratometry: Km; maximum keratometry: Kmax), inferior superior value (IS-value), BAD, and TKC (a classification system of keratoconus as provided by Pentacam HR) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Corneal topography and tomography were obtained through Pentacam HR (Oculus, Wetzlar, Germany), which uses the Scheimpflug imaging technique to present indices with acceptable accuracy and repeatability ( 23 ). The following parameters were evaluated in the current study: corneal thickness (apex corneal thickness: ACT; pupil corneal thickness: PCT; thinnest corneal thickness: TCT), keratometry (flat keratometry: K1; steep keratometry: K2; mean keratometry: Km; maximum keratometry: Kmax), inferior superior value (IS-value), BAD, and TKC (a classification system of keratoconus as provided by Pentacam HR) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“… 21 Likewise, other studies reported good KC detection ability using corneal dynamic response parameters from the Corvis ST with linear regression models and random forests. 13 , 15 It is noteworthy that these parameters are directly generated by the Ocular Response Analyzer or Corvis ST, and the dependency of the diagnostic model on the device may affect the general applicability of the model. Furthermore, it has also been demonstrated that, if there is a correlation between parameters, both the accuracy and consistency of the model predictions are compromised.…”
Section: Discussionmentioning
confidence: 99%
“… 11 13 Moreover, previous studies have found correlations only between KC and certain biomechanical indices, and to date, no diagnostic model has been found to directly diagnose KC based on corneal biomechanical alterations. 14 , 15 The current study, with the aid of ML approaches, attempts to analyze the corneal dynamic deformation process to diagnose KC solely from a corneal biomechanical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation amplitude (DA) is defined as the greatest inward dislocation of the corneal apex measured at the highest concavity (HC) point [11]. DA ratio of central and peripheral deflection is assessed in a distance of 1 mm and 2 mm resulting in DAR-1 and DAR-2 parameters and stiffness parameter at the 1 st applanation (SPA1) [12]. Applanation lengths (AL) and corneal velocities (CVel) are measured in inward and outward phases.…”
Section: Methods Of Corneal Biomechanical Properties Assessmentmentioning
confidence: 99%
“…The curvature radius at the highest concavity (curvature radius HC) integrated inverse radius (IntInverseR) and maximum inverse radius (InverseR) are also documented. The higher values of IR, the lower corneal resistance to deformation what indicate lower corneal stiffness [12]. Corneal pachymetry (Pachy) and parameters essential in potential keratoconus detection such as Ambrosio Rational Thickness horizontal (ARTh) and Pachyslope are measured before the air-puff generation [12].…”
Section: Methods Of Corneal Biomechanical Properties Assessmentmentioning
confidence: 99%